Identification of a Novel Force-Generating Protein, Kinesin, Involved in Microtubule-Based Motility - Vale, Ronald D. (1985)
Axoplasm from the squid giant axon contains a soluble protein translocator that induces movement of microtubules on glass, latex beads on microtubules, and axoplasmic organelles on microtubules. We now report the partial purification of a protein from squid giant axons and optic lobes that induces these microtubule-based movements and show that there is a homologous protein in bovine brain. The purification of the translocator protein depends primarily on its unusual property of forming a high affinity complex with microtubules in the presence of a nonhydrolyzable ATP analog, adenylyl imidodiphosphate. The protein, once released from microtubules with ATP, migrates on gel filtration columns with an apparent molecular weight of 600 kilodaltons and contains 110–120 and 60–70 kilodalton polypeptides. This protein is distinct in molecular weight and enzymatic behavior from myosin or dynein, which suggests that it belongs to a novel class of force-generating molecules, for which we propose the name kinesin.